2019
DOI: 10.32598/ijt.13.3.595.1
|View full text |Cite
|
Sign up to set email alerts
|

Neurobehavioral Effects of Prolonged Exposure to Solid Air Freshener in Mice

Abstract: Background: Air fresheners are products with fragrances used to mask unpleasant odor in the environment. However, air fresheners contain diverse chemical substances that pose health challenges to the users; hence are of public health significance. Although previous studies have shown that air fresheners affect the lungs, liver and reproductive organs, the neurobehavioral effects of these agents are yet to be evaluated in details. This study evaluated the neurobehavioral effects and biochemical changes in mice … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
1
1
Order By: Relevance
“…Similarly, mice exposed to 1,000 ppm toluene showed reduction in the recognition index, though reduction was only significant in the groups of mice exposed to 2,000-6,000 ppm toluene (Montes et al 2017). Prolonged exposure to high doses of air freshener containing toluene caused significant memory dysfunction in mice, while no changes were observed in lower doses (Umukoro et al 2021). As opposed to the present study, the study by Chan et al (2019) administered toluene in mice 30 min before the NOR test.…”
Section: Effect Of Nigella Sativa Supplementations and Toluene On Rec...contrasting
confidence: 82%
“…Similarly, mice exposed to 1,000 ppm toluene showed reduction in the recognition index, though reduction was only significant in the groups of mice exposed to 2,000-6,000 ppm toluene (Montes et al 2017). Prolonged exposure to high doses of air freshener containing toluene caused significant memory dysfunction in mice, while no changes were observed in lower doses (Umukoro et al 2021). As opposed to the present study, the study by Chan et al (2019) administered toluene in mice 30 min before the NOR test.…”
Section: Effect Of Nigella Sativa Supplementations and Toluene On Rec...contrasting
confidence: 82%
“…This difference with the conclusions of this HRA can be explained by the differences in the selected toxicity values and by the higher maximum exposure levels determined in the present study. However, other types of studies have concluded that exposure to noncombustible air fresheners could be of concern: the measured concentrations could exceed the thresholds associated with the exacerbation of existing symptoms in people with asthma, 27,35,36 and certain epidemiological studies have identified a significant association between the use of some air fresheners and respiratory disorders during the first years of life, 37 a higher risk of breast cancer 38 and a short‐term decrease in lung ventilation capacity, 39 while toxicological studies have reported a significant association between the application of certain air fresheners and inflammatory phenomena in rats, 40 neurobehavioral effects in rats, 41 and adverse effects on the liver cells in young rats 42 . A literature review demonstrated a significant association between the use of noncombustible air fresheners and certain health effects (disorders of the respiratory system) but no causal relation was identified, 25 and other reviews indicated that the available data are insufficient to draw conclusions on the potential health effects associated with aerosol sprays 43 and essential oil air fresheners, 44 while a European collective expert assessment concluded that certain noncombustible air fresheners may cause or aggravate symptoms in highly sensitive persons and may be of concern in children 8 .…”
Section: Discussionmentioning
confidence: 99%